The night train & the golden bird - Meinke, Peter (Pitt poetry series, 1977)
Although The Night Train and the Golden Bird is Peter Meinke's first poetry collection, it is a seasoned performance-the result of careful deliberation and mature judgment-yet impetuous and exciting. It's full of wit and humor tempered with the sadness of approaching middle-age, anguish over political and social injustice, and of the very failings of everyday people and their lives.